Delayed diagnosis of a patient with Usher syndrome 1C in a Louisiana Acadian family highlights the necessity of timely genetic testing for the diagnosis and management of congenital hearing loss. (8th December 2017) - Umrigar, Ayesha; Musso, Amanda; Mercer, Danielle; Hurley, Annette; Glausier, Cassondra; Bakeer, Mona; Marble, Michael; Hicks, Chindo; Tsien, Fern
Advances in sequencing technologies and increased understanding of the contribution of genetics to congenital sensorineural hearing loss have led to vastly improved outcomes for patients and their families. Next-generation sequencing and diagnostic panels have become increasingly reliable and less expensive for clinical use. Despite these developments, the diagnosis of genetic sensorineural hearing loss still presents challenges for healthcare providers. Inherited sensorineural hearing loss has high levels of genetic heterogeneity and variable expressivity. Additionally, syndromic hearing loss (hearing loss and additional clinical abnormalities) should be distinguished from non-syndromic (hearing loss is the only clinical symptom). Although the diagnosis of genetic sensorineural hearing loss can be challenging, the patient's family history and ethnicity may provide critical information, as certain genetic mutations are more common in specific ethnic populations. The early identification of the cause of deafness can benefit patients and their families by estimating recurrence risks for future family planning and offering the proper interventions to improve their quality of life. Collaboration between pediatricians, audiologists, otolaryngologists, geneticists, and other specialists are essential in the diagnosis and management of patients with hearing disorders. An early diagnosis is vital for proper management and care, as some clinical manifestations of syndromic sensorineural hearing loss are not apparent at birth and have a delayed age of onset. We present a case of Usher syndrome (congenital deafness and childhood-onset blindness) illustrating the challenges encountered in the diagnosis and management of children presenting with congenital genetic sensorineural hearing loss, along with helpful resources for clinicians and families.